2023
DOI: 10.1097/js9.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison of bone resection margin distances in virtual surgical planning versus histopathology: a prospective study

Jane J. Pu,
Anthony W. I. Lo,
May C. M. Wong
et al.

Abstract: Background: Positive bone margins have been shown to be associated with worse locoregional control and survival performance in oral oncology patients. With the application of computer-assisted surgery (CAS) and patient-specific surgical guides, we can accurately execute the preoperative osteotomy plan. However, how well we can predict the margin distance in the final histopathology with a preoperative CT scan, the factors associated with it, and how much leeway we should spare when designing the os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…It must be pointed out that patient-specific planning requires more time than a lack of planning, for the PSR company and/or for the surgeon, but various articles and common sense suggest that planned surgery provides better outcomes than unplanned surgery [71,72]. Additionally, the planning should be prepared before the surgical procedure, allowing for the surgeon to concentrate on planning when outside the operating room and on the patient once inside [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that patient-specific planning requires more time than a lack of planning, for the PSR company and/or for the surgeon, but various articles and common sense suggest that planned surgery provides better outcomes than unplanned surgery [71,72]. Additionally, the planning should be prepared before the surgical procedure, allowing for the surgeon to concentrate on planning when outside the operating room and on the patient once inside [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…CAD/CAM systems require the establishment of oncologic margins preoperatively in order to produce anatomic models and cutting guides. While there was initial uncertainty regarding the control of locoregional disease with preplanned margins, several studies have shown similar rates of negative intraoperative and final margins, as well as short and long-term recurrences 2 , 21 . Oncological safety of the method is now established, but requires presurgical evaluation of margins on recent CT and MRI, that too much time does not pass between planning and surgery, accurate correlation of the clinical and radiological data, and preoperative collaboration of ablative and reconstructive surgeons via videoconference.…”
Section: Reduced Rate Of Complicationsmentioning
confidence: 99%